2006
DOI: 10.1111/j.1471-4159.2005.03635.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling reveals that peripheral nerve regeneration is a consequence of both novel injury‐dependent and reactivated developmental processes

Abstract: One of the most striking features of the injured mature peripheral nervous system is the ability to regenerate. The lesioned peripheral nervous system displays stereotypic histopathological reactions indicating the activation of a co-ordinated lesion-induced gene expression programme. Previous research has already identified molecular components of this axonal switch from a mature transmitting to a regenerative growth mode. The observed alterations in gene expression within the lesioned distal nerve stump were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
110
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(121 citation statements)
references
References 66 publications
11
110
0
Order By: Relevance
“…Axons begin to grow into the distal endoneurial tubes 1 week after nerve injury [6,39,45] ; Schwann cell/axon contacts are re-established and remyelination occurs at about 2 weeks; and the proper target tissues are reinnervated at about 4 weeks after sciatic nerve injury. In this process, a large number of genes with marked up-or down-regulation were differentially expressed, indicating sustained regulation at consecutive time points, meaning regeneration/repair by means of a continuously progressive program [4,10,35] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Axons begin to grow into the distal endoneurial tubes 1 week after nerve injury [6,39,45] ; Schwann cell/axon contacts are re-established and remyelination occurs at about 2 weeks; and the proper target tissues are reinnervated at about 4 weeks after sciatic nerve injury. In this process, a large number of genes with marked up-or down-regulation were differentially expressed, indicating sustained regulation at consecutive time points, meaning regeneration/repair by means of a continuously progressive program [4,10,35] .…”
Section: Discussionmentioning
confidence: 99%
“…In this process, a large number of genes with marked up-or down-regulation were differentially expressed, indicating sustained regulation at consecutive time points, meaning regeneration/repair by means of a continuously progressive program [4,10,35] . Nerve regeneration mainly consists of nerve repair and tissue re-innervation after injury [45,46] . The activated injury-dependent process is regulated initially following the genetic response featuring degeneration and regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…However, what is critical for the biology of regeneration and for a possible regeneration therapeutic agent is whether the underlying molecular profile of CNS regeneration recapitulates the molecular profile of neurodevelopment. Initial transcriptional profiling of neurons that form new connections after stroke, retinal ganglion cells that regenerate an injured axon in the optic nerve, or dorsal root ganglion cells that regrow a connection after peripheral nerve injury suggest some overlap with genes that are active in the developing nervous system, but overall a distinct set of genes that is regulated in these injury responses 11, 122. However, direct comparison of the transcriptome of neurons exposed to a regenerating stimulus after stroke and the transcriptomes of neurons at several stages of neuronal development from many different laboratories clearly indicates that the molecular expression profile of regeneration is statistically and fairly dramatically distinct from the developmental transcriptome 13.…”
Section: Regeneration Does Not Recapitulate Developmentmentioning
confidence: 99%
“…Lesioning the peripheral axonal branches of DRG neurons causes expression of a distinct set of genes, termed regeneration-associated genes, which are not upregulated after central lesioning (Ylera and Bradke, 2006). Interestingly, those sets of genes contain direct and indirect regulators of microtubule polymerization and stabilization, including tubulin isoforms, MAPs (microtubule- associated proteins), and arginase I (Miller et al, 1989;Moskowitz and Oblinger, 1995;Cai et al, 2002;Bosse et al, 2006), which may enhance the rapid regrowth of lesioned PNS axons. Notably, it has been demonstrated that interfering with the expression of microtubule binding proteins inhibits neurite outgrowth (Caceres et al, 1992).…”
Section: Putative Signaling Mechanisms Underlying Microtubule Disorgamentioning
confidence: 99%